Diagenesis and Origination of Carbonate Cements in Deeply Buried Sandstones of the Eocene Es3 Member, Raoyang Sag, Bohai Bay Basin, China. (20th November 2020) - Zhang, Kaixun; Fang, Xinxin; Xie, Ying; Guo, Shun; Liu, Zhenwang; Wang, Lei
Abstract : Diagenesis is one of the most predominant factors controlling reservoir quality in the deeply buried siliciclastic sandstones of the third member in the Eocene Shahejie Formation (Es3 ), in the Raoyang Sag, the Bohai Bay Basin. In this study, thin section, cathodoluminescence (CL), scanning electron microscope (SEM), X-ray diffraction (XRD), Raman spectrum, carbon and oxygen isotopes, and fluid inclusion analyses are used to restructure paragenetic sequences and detect origins of carbonate cements recorded in this deeply buried member. Based on petrographic analyses, the Es3 sandstones are identified as lithic arkoses and feldspathic litharenites at present, but derived from original arkoses and lithic arkoses, respectively. Geohistorically, the Es3 sandstones have undergone two diagenetic episodes of eogenesis and mesogenesis. Events observed during eogenesis include chemical compaction, leaching of feldspar, development of chlorite coating and kaolinite, precipitation of the first generation of quartz overgrowth (QogI), dissolution of feldspar, and precipitation of calcite and nonferroan dolomite cement. Mesogenetic alterations include chemical compaction, precipitation of kaolinite aggregate and the second generation of quartz overgrowth (QogII), precipitation of ankerite, development of I/S and illite, and formation of pyrite. Carbon and oxygen isotopic data show that calcite cements are characterized by 13 C (δ 13 C PDB ranging from -0.7‰ to 1.0‰ with an average of 0.1‰) and 18 O (δ 18 O SMOW varying from 12.3‰ to 19.0‰ with an average of 16.2‰); these stable isotopic data combined with Z value (from 114.69 to 122.18) indicate skeletal debris (δ 13 C PDB ranging from -1.2‰ to -1.1‰ with an average of -1.15‰; δ 18 O SMOW varying from 23.0‰ to 23.2‰ with an average of 23.1‰) and ooids in adjacent carbonate beds involved in meteoric water and seawater from outside jointly served as the carbon sources. For nonferroan dolomite, the δ 13 C PDB value of -4.1‰ is a little bit negative than the calcite, and the δ 18 O SMOW of 14.3‰ is coincident with the calcite, which suggest the nonferroan dolomites come from the diagenetic fluids with a similar oxygen isotopic composition to that of the calcite but modified by the external acidic δ 13 C-depleted water. However, the ankerites are actually rich in 12 C (δ 13 C PDB ranging from -10.0‰ to -1.2‰, mean = − 4.3 ‰ ) and 16 O (δ 18 O SMOW varying from 10.1‰ to 19.4‰, mean = 14.9 ‰ ), when combined with the distribution of cutting down along the direction pointing to sand-body center from the margin and microthermometric temperature (Th's) data mainly varying between 115.2°C and 135.5°C with an average of 96.0°C, indicating the main origination from the Es3 source rocks with effective feldspar buffer action for the acidic fluids in the margins of the Es3 sandstones. In addition, the necessary elements for ankerite such as Fe 2+, Ca 2+, and Mg 2+ ions also come from organic matter and clay minerals during thermal maturation of the Es3 source rocks. The study provides insights into diagenetic processes and origination of carbonate cements in the Es3 sandstones; it will facilitate the cognition of predictive models of deeply buried sandstone reservoirs to some extent, which can reduce the risks involved in oil and gas exploration and development.